2023
DOI: 10.5853/jos.2022.03552
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ischemic Stroke in Patients With Atrial Fibrillation Receiving Non-Vitamin K Oral Anticoagulants: Causes and Prevention Strategies

Abstract: Atrial fibrillation (AF) is a leading cause of cardioembolic stroke, which is often fatal or disabling. Prevention of stroke is crucial in AF management, and anticoagulation with non-vitamin K oral anticoagulants (NOACs) is the mainstay of AF management for stroke prevention. Because NOAC prescriptions have been surging worldwide, the development of acute ischemic stroke in patients with AF who receive NOAC treatment is an increasingly important issue in clinical practice. Moreover, these patients show a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…During the last decade, our knowledge on AIS in patients with preceding DOAC treatment has vastly expanded [ 19 ]. Although AIS can occur even despite sufficient anticoagulation, a number of causes for DOAC treatment failure have been identified and researched [ 4 , 5 ]. Our study shows that a potential cause of AIS occurring in DOAC-treated patients can be identified in most cases and in many of them prevented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the last decade, our knowledge on AIS in patients with preceding DOAC treatment has vastly expanded [ 19 ]. Although AIS can occur even despite sufficient anticoagulation, a number of causes for DOAC treatment failure have been identified and researched [ 4 , 5 ]. Our study shows that a potential cause of AIS occurring in DOAC-treated patients can be identified in most cases and in many of them prevented.…”
Section: Discussionmentioning
confidence: 99%
“…With growing numbers of patients receiving DOAC in primary and secondary stroke prevention, the number of cases of AIS occurring in DOAC-treated patients is also increasing [ 4 , 8 ], making it important to continuously analyse their incidence, potential causes, clinical course, and outcomes.…”
Section: Clinical Rationale For the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Asian patients are considered at high risk of hemorrhage and off-label dosage, especially under-dose of NOACs, is regularly prescribed by domestic physicians to patients with AF ( Cheng et al, 2019 ). Poor compliance with guidelines and off-label use of NOACs could cause adverse outcomes ( Bang et al, 2023 ). It is important to highlight compliance with anticoagulation therapy in alignment with guidelines and medication labels in practical clinical settings.…”
Section: Introductionmentioning
confidence: 99%